2006
DOI: 10.1038/sj.mp.4001891
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol dependence is associated with the ZNF699 gene, a human locus related to Drosophila hangover, in the Irish affected sib pair study of alcohol dependence (IASPSAD) sample

Abstract: Because tolerance is an important aspect of alcohol dependence (AD) in humans, recent evidence showing that the Drosophila gene hang is critically involved in the development of alcohol tolerance in the fly suggests that variation in related human loci might be important in the etiology of alcohol-related disorders. The orthology of hang in mammals is complex, but a number of human gene products (including ZNF699) with similar levels of amino-acid identity (18-26%) and similarity (30-41%), are consistently ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 39 publications
0
20
0
Order By: Relevance
“…ZNF699 is one of the human homologs of the hangover gene, and in an Irish sib pair study, polymorphisms in ZNF699 were associated with alcohol dependence. One of the dependence-associated haplotypes also showed decreased ZNF699 gene expression in the dorsolateral prefrontal cortex in postmortem tissue (Riley et al, 2006).…”
Section: Stress Responsesmentioning
confidence: 97%
“…ZNF699 is one of the human homologs of the hangover gene, and in an Irish sib pair study, polymorphisms in ZNF699 were associated with alcohol dependence. One of the dependence-associated haplotypes also showed decreased ZNF699 gene expression in the dorsolateral prefrontal cortex in postmortem tissue (Riley et al, 2006).…”
Section: Stress Responsesmentioning
confidence: 97%
“…Polymorphisms in the human ALK gene are correlated with multiple measures of ethanol sensitivity (Lasek et al 2011b), and polymorphisms in one human homolog of hang , ZNF699 , were found to be associated with alcohol dependence (Riley et al 2006). Recently, a genome-wide meta-analysis revealed that polymorphisms in autism susceptibility candidate 2 ( AUTS2 ) are associated with alcohol consumption (Schumann et al 2011).…”
Section: Mammalian Validation Of Mechanisms Underlying Ethanol-inducementioning
confidence: 99%
“…Genetic and pharmacologic studies indicate that rapid tolerance in Drosophila requires the integrity of octopaminergic and γ-aminobutyric acid B (GABA B ) receptor pathways, a large conductance calcium-sensitive potassium (BK) channel, the Homer neuronal adaptor protein, and a novel stress pathway defined by the gene hangover (Cowmeadow et al, 2005; Dzitoyeva et al, 2003; Scholz et al, 2005; Urizar et al, 2007). Thus, at least some of the neurotransmitter and signaling systems that mediate these behaviors are evolutionarily conserved (e.g., the GABA B and BK-type potassium channels; Pietrzykowski et al, 2004; Zaleski et al, 2001), and studies in flies can provide novel candidate genes for mammalian and human studies (Riley et al, 2006). …”
mentioning
confidence: 99%